Conjugacy class sizes for some 2-groups of nilpotency class two - Ilangovan, Sheila (Penerbit UTM Press, 2012)
In this paper, we investigate the irreducible characters and the conjugacy class sizes for some 2-groups of class 2. The size of conjugacy classes of an element x in a group G is the order of xG, where xG is the conjugacy classes containing x. This research is based on the classification of those groups given by Magidin in 2006. We show that the conjugacy class sizes of G are 2ρ where 0 ≤ ρ ≤ γ and pipeG'{pipe} = 2γ.